Serum HER 2 extracellular domain level is correlated with tissue HER 2 status in metastatic gastric or gastro-oesophageal junction adenocarcinoma. - Shu-Qin Dai; Xin An; Fang Wang; Qiong Shao; Yong-Chang Chen; Ya-Nan Kong; Cui Chen; Cong Li; Hui-Yan Luo; Ying Liang; Feng-Hua Wang; Rui-Hua Xu; et al. (PLoS ONE, 2013)
BACKGROUND: To explore the association between serum human epidermal growth factor receptor 2 (HER 2) extracellular domain (ECD) levels and tissue HER 2 status in metastatic gastric cancer. PATIENTS AND METHODS: HER 2 status was retrospectively analyzed in 219 advanced gastric or gastroesophageal junction (GEJ) patients. Serum HER 2 ECD was measured by chemiluminescent assay and tissue HER 2 was assessed by fluorescent in situ hybridisation (FISH) and immunohistochemistry (IHC) assay. RESULTS: Significant associations were found between serum HER 2 ECD levels and tissue HER 2 status. Twenty-four patients had HER 2 ECD levels >16.35 ng/mL, which has a sensitivity of 51.4% and a specificity of 97.3% to predict tissue HER 2 status. When the cut-off value was increased to 22 ng/mL, then all 12 patients with serum HER 2 ECD levels>22 ng/mL were tissue HER 2 positive, corresponding to a specificity of 100% and a sensitivity of 32.4%. High serum HER 2 ECD levels were strongly associated with the intestinal histological type (Lauren's classification), liver metastasis, multiple metastasis (>2) and increased LDH levels, but not with overall survival. CONCLUSIONS: The high specificity of the serum HER 2 ECD assay in predicting tissue HER 2 status suggests its potential as a surrogate marker of the HER 2 status in gastric cancer.